410 A simple surgical technique of groin dissection in genitourinary cancers: A single centre experience. (13th November 2020) - Kumar, N; Ray, MD
Abstract : Introduction: Groin dissection is associated with varying morbidities. Various incision modifications have been described in the literature but to date, morbidity still ranges widely up to 30–52%. Thereby, this study aims to share our experience with the new technique. Methods: We used 'River Flow incision' technique for 188 groin dissections surgeries in consecutive 104 (bilateral in 84 and unilateral in 20) patients from July 2012 to June 2019. Two, 5–7 cm curvilinear incisions parallel to inguinal ligament were made and flap raised keeping the dissection level just below the membranous layer of the groin (figure 1 A, B). Results: The median lymph nodes harvested were 10 on both sides (range: 7–15). The median operative time was 80 min (range 60–90) and blood loss was approximately 25 ml (range: 20–35 ml). There was no treatment specific peri-operative mortality. None of the patients had flap necrosis. Seroma formation was the most common complication, observed in 26 (13.8%), skin edge necrosis in 22 (11.7%) including surgical wound infection in 13 (6.9%) cases. During the routine follow-up, six had (3.2%) persisting seroma, five (2.6%) had grade II lymphedema and two developed deep venous thrombosis (1.06%). Eleven patients (5.8%) developed recurrence during the follow-up period. Six patients had locoregional recurrence, while 5 patients (3.2%) developed systemic recurrence. The femoral artery blows out was not observed in any patient even after receiving radiotherapy. Conclusion: This modified technique reduced the all possible morbidities without compromising oncological principles. It can be reproducible and feasible with a comparable learning curve.